2011
DOI: 10.1111/j.1398-9995.2011.02747.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression is differently affected by pimecrolimus and betamethasone in lesional skin of atopic dermatitis

Abstract: The gene expression profiles are consistent with our previous findings that corticosteroids may exert a more potent anti-inflammatory effect but may impair the restoration of the skin barrier. Corticosteroids are still the main treatment for severe and acutely exacerbated AD; pimecrolimus may be preferable for long-term treatment and stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 36 publications
2
74
0
3
Order By: Relevance
“…A recent study of the gene expression profiles of a topical steroid (betamethasone) and pimecrolimus demonstrated differences between the two substances, in particular in relation to epidermal genes [27]. In contrast to the steroid, pimecrolimus led to full restoration of the skin barrier [27], which is certainly beneficial and might be an explanation for the healing of PN lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of the gene expression profiles of a topical steroid (betamethasone) and pimecrolimus demonstrated differences between the two substances, in particular in relation to epidermal genes [27]. In contrast to the steroid, pimecrolimus led to full restoration of the skin barrier [27], which is certainly beneficial and might be an explanation for the healing of PN lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Topical steroids result in rapid improvement of skin inflammation and pruritus, but have opposing effects on barrier functions [95,99,100]. Positive effects of topical corticosteroids on the skin barrier include the increase of SC hydration, decrease of TEWL, and normalization of filaggrin and loricrin expression [95,100,101]. However, human studies and animal models demonstrated that long-term application of local glucocorticoids resulted in significant impairment of epidermal barrier function and homeostasis.…”
Section: Topical Glucocorticosteroidsmentioning
confidence: 99%
“…This multidimensional approach could ultimately lead to the development of disease-specific multiplex diagnostic and/or predictive tools in the future such as RNA-profiling upon distinct therapeutic approaches (114). However, even at this early stage, we can already learn from the acquired knowledge and make a tentative proposal for molecular taxonomy and the clinical value of this information as depicted in Fig.…”
Section: Thymus and Activation-regulated Chemokine (Ccl17/tarc)mentioning
confidence: 99%